PENINGKATAN MANAJEMEN SISTEM INFORMASI DAN UJI KOMPETENSI MAHASISWA MELALUI RANCANG BANGUN SISTEM INFORMASI DAN UJI KOMPETENSI LSP POLMED - Kadri Yusuf; Rihat Sebayang; Infarizal Infarizal (STMIK KAPUTAMA, 2021)
This study makes information management and online registration of student competency tests through the design of Polmed Siukom. The target of this research is the availability of an information system and online registration of the Medan State Polytechnic Student Competency Test, abbreviated as the Siukom Police, which can be used as a service facility for information activities and a competency test data base as well as an online registration process. Student competency tests are conducted by the Medan State Polytechnic academic community. This research activity involved several related units within the Medan State Polytechnic, namely the Professional Certification Institute (LSP), the Medan State Polytechnic Information System Center (PSI), the Leadership Element consisting of the Director, Deputy Director I, Deputy Director II, and Deputy Director IV. The fundamental contribution of this research is the formation of public service management for the Medan State Polytechnic academic community in the field of website-based Student Competency Test which will be used as a means of community service. This research uses descriptive analytical method, with a qualitative approach to obtain information and collect the required data